Prepandemic inequalities in the burden of disease in Scotland due to multiple deprivation: a retrospective study - Fatim Lakha; Grant M A Wyper; Ian Grant; Eilidh Fletcher; Diane Stockton; Neil Chalmers (BMJ Publishing Group, 2023)
Background Health inequalities in Scotland are well documented, including the contribution of different causes to inequalities in mortality. Our aim was to estimate inequalities within a burden of disease framework, accounting for both premature mortality and the effects of morbidity, to understand the contribution of specific diseases to health inequalities prior to the COVID-19 pandemic.Methods Disability-adjusted life-years (DALYs) for 70 individual causes of disease and injury were sourced from the Scottish Burden of Disease Study. Area-level deprivation was measured using the Scottish Index of Multiple Deprivation. Inequalities were measured by the range, Relative Index of Inequality, Slope Index of Inequality and attributable DALYs were estimated by using the least deprived decile as a reference.Results The overall disease burden was double that in the most deprived areas (50 305 vs 20 955 DALYS per 100 000), largely driven by inequalities in premature mortality. The rate in the most deprived areas was around 48% higher than the mean population rate (Relative Index of Inequality=0.96), with 35% of DALYs attributed to differences in area-based deprivation. Many leading causes of disease burden in 2019-heart disease, drug use disorders, lung cancer and chronic obstructive pulmonary disease-were also the leading drivers of absolute and relative inequalities in the disease burden.Conclusion Our study evidences the extent of the stark levels of absolute and relative inequality prior to the COVID-19 pandemic. Given prepandemic stalling of mortality trend improvements and widening health inequalities, and the exacerbation of these caused by COVID-19, urgent policy attention is required to address this.